Left, right and presidential elections in Brazil - Tarouco, Gabriela (Estudos Avançados, 2022)
The article analyzes data from electoral programs for presidential elections in Brazil from 1994 to 2018 to describe how candidates stand on the ideological scale. The data produced and made available by the Manifesto Project allow measuring their leftist and rightist content and its variation over time. The analysis shows that leftist and rightist content coexist side by side in the platforms while confirming the ideological distinction among the alternatives. In addition, it applies ideology measures to compute and compare the polarization index in each election and shows its sudden increase in 2018.